Role of Basic Fibroblast Growth Factor in Cancer: Biological Activity, Targeted Therapies, and Prognostic Value - Alessio Ardizzone; Valentina Bova; Giovanna Casili; Alberto Repici; Marika Lanza; Raffaella Giuffrida; Cristina Colarossi; Marzia Mare; Salvatore Cuzzocrea; Emanuela Esposito; Irene Paterniti (Cells, 2023)
Cancer is the leading cause of death worldwide; thus, it is necessary to find successful strategies. Several growth factors, such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF, FGF2), and transforming growth factor beta (TGF-β), are involved in the main processes that fuel tumor growth, i.e., cell proliferation, angiogenesis, and metastasis, by activating important signaling pathways, including PLC-γ/PI3/Ca2+ signaling, leading to PKC activation. Here, we focused on bFGF, which, when secreted by tumor cells, mediates several signal transductions and plays an influential role in tumor cells and in the development of chemoresistance. The biological mechanism of bFGF is shown by its interaction with its four receptor subtypes: fibroblast growth factor receptor (FGFR) 1, FGFR2, FGFR3, and FGFR4. The bFGF–FGFR interaction stimulates tumor cell proliferation and invasion, resulting in an upregulation of pro-inflammatory and anti-apoptotic tumor cell proteins. Considering the involvement of the bFGF/FGFR axis in oncogenesis, preclinical and clinical studies have been conducted to develop new therapeutic strategies, alone and/or in combination, aimed at intervening on the bFGF/FGFR axis. Therefore, this review aimed to comprehensively examine the biological mechanisms underlying bFGF in the tumor microenvironment, the different anticancer therapies currently available that target the FGFRs, and the prognostic value of bFGF.